Clinicopathological Features of Oral Leukoplakia Among Snuff Users and Non-Users: An Analytical Study: Clinicopathological Features of Oral Leukoplakia - Naushin, Tehmina; Khan, Abbas Saleem; Alam, Sadaf; Motahir, Nasiha; Fatima Iqbal; Younas, Hoor Maryam; Mahmood , Sidra; Mahmood, Uzma (Pakistan Journal of Health Sciences, 2023)
Oral leukoplakia refers to a white lesion of questionable risk excluding other lesions carrying a risk of conversion into malignancy. Tobacco is regarded as the most common risk factor and may affect the clinicopathological aspect of the said lesion. Objectives: To check the clinicopathological features of oral leukoplakia among snuff users and non-users. Methods: The present analytical study was done on 60 oral leukoplakia cases and was further subdivided into 30 cases of snuff users and 30 non users. Clinicopathological features were assessed in all the cases. Data analysis were done by using SPSS-20. Results: The observed male cases were 43 (71.7 %) and female cases were 17 (28.3%). The ratio was found to be 2.5:1. All the 30 snuff users were males. Among non-users 13/30 (43.3%) were males and 17/30 (56.7%) were females. The relationship was found to be statistically significant with a p-value of <0.01. The mean age among cases who used snuff was 56.97 (SD ± 14.71) while the mean age among non-users was found to be 47.43 (SD ± 13.44). In snuff user’s buccal mucosa was affected in 12/30 (40%) cases whereas in non-user buccal mucosa was also the most common site 18/30 (60%) cases showing a non-significant relationship p-value 0.59. Conclusions: Oral leukoplakia was more prevalent among males with a mean age range of more than fifty years and buccal mucosa and buccal sulcus being the most common sites. Dysplastic epithelium was more common among those cases that used snuff and this showed that chances of malignant transformation are more in such cases.